2016
DOI: 10.3109/21679169.2016.1174297
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the validity and reliability of a smartphone pedometer application

Abstract: The aim of this study was to investigate the validity and measurement agreement of a smartphone pedometer application and a traditional pedometer, both compared to manual step count, in six environments. The study also examined the relative reliability of two positions of the smartphone pedometer application in the six environments. Twenty participants carried two smartphones (iPhone 4S) with the same pedometer application (Pedometer FREE GPSþ) in two device positions together with a traditional pedometer (Yam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…The way the phone is carried during self-selected walking speed does not affect the results. They were comparable when the phone was carried in a backpack or a handbag [15] or in the chest or pants pocket [16], indicating that the phone need not be carried in a back trouser pocket, as previously suggested [15]; therefore, people can carry them in whichever way they are accustomed to [8].…”
Section: Introductionmentioning
confidence: 51%
See 1 more Smart Citation
“…The way the phone is carried during self-selected walking speed does not affect the results. They were comparable when the phone was carried in a backpack or a handbag [15] or in the chest or pants pocket [16], indicating that the phone need not be carried in a back trouser pocket, as previously suggested [15]; therefore, people can carry them in whichever way they are accustomed to [8].…”
Section: Introductionmentioning
confidence: 51%
“…There are few research reports assessing smartphone accuracy during stair climbing. Previous reports consistently showed increased error, specifically decreased accuracy of pedometers [13] as well as smartphone pedometers [13,16].…”
Section: Discussionmentioning
confidence: 75%
“…Evidence for the measurement accuracy of step counter apps is mixed. Some studies have demonstrated that apps can provide valid step counts [67][68][69], whereas others have found that they underestimate step counts, mainly because people do not always carry their phones on their person throughout the day [70][71][72][73]. Nevertheless, meta-analyses have indicated that app-based PA interventions can significantly increase the daily step count in adult populations [74][75][76].…”
Section: Data Collection Methodsmentioning
confidence: 99%
“…To meet the WHO goal by 2030, new efforts and methods are needed to be able to change PB behavior. There are a number of studies conducted in relation to increasing PA (Ball et al, 2017;Conn et al, 2011;Tuso, 2015), decreasing SB (Gardner et al, 2016;Kozey-Keadle et al, 2011;Lewis et al, 2017;Nigg et al, 2017), and that aim to monitor or change the activity pattern using different kinds of self-monitoring technologies or devices (Åkerberg et al, 2016;Bravata et al, 2007;de Vries et al, 2016;Hellstrom et al, 2018;Nigg et al, 2017;Romeo et al, 2019). There are also many cross-sectional studies performed where patterns regarding PA and/or SB are mapped or investigated on a population level in different countries (Barker et al, 2019;Hagströmer, 2007;Howitt et al, 2016;Mengesha et al, 2019).…”
Section: Introductionmentioning
confidence: 99%